Supraventricular tachycardia and acute confusion following ingestion of e-cigarette fluid containing AB-FUBINACA and ADB-FUBINACA: a case report with quantitative analysis of serum drug concentrations. (9th August 2017) - Lam, Rex Pui Kin; Tang, Magdalene Huen Yin; Leung, Siu Chung; Chong, Yeow Kuan; Tsui, Matthew Sik Hon; Mak, Tony Wing Lai
Abstract: Background: AB-FUBINACA and ADB-FUBINACA are structurally similar synthetic cannabinoids with potent CB1 receptor agonistic effects. Very little is known about their pharmacology and toxicology. Objective: To report a case of supraventricular tachycardia and acute confusion after ingestion of e-cigarette fluid containing AB-FUBINACA and ADB-FUBINACA, with quantitative analysis of the serum drug concentrations. Case report: A healthy 24-year-old man ingested two drops of e-cigarette fluid which were later found to contain AB-FUBINACA and ADB-FUBINACA. Within 30 min of ingestion, he became somnolent, confused, and agitated, with palpitation and vomiting. On arrival to the emergency department, a short run of supraventricular tachycardia was noted, which resolved spontaneously. Bedside urine immunoassay failed to detect recreational drugs. Laboratory blood tests showed mild hypokalemia. Exposure to AB-FUBINACA and ADB-FUBINACA was confirmed analytically, with serum concentrations of 5.6 ng/mL and 15.6 ng/mL, respectively, in the blood sample collected on presentation. The patient recovered uneventfully with supportive treatment and was discharged 22 h after admission. Discussion: AB-FUBINACA and ADB-FUBINACA are orally bioavailable with rapid onset of toxicity after ingestion. In this case, supraventricular tachycardia was likely the result of exposure to AB-FUBINACA and ADB-FUBINACA. The serum concentrations of AB-FUBINACA and ADB-FUBINACA were higher than those previously reported in fatal cases. Conclusion: In the context of acute poisoning, the presence of unexplained tachyarrhythmias, confusion, and a negative recreational drug screen should prompt clinicians to consider synthetic cannabinoid toxicity as a differential diagnosis.